Lymphoma with superimposed tuberculosis and fungal infection mimicking parapharyngeal abscess complicated with recurrent neurocardiogenic syncope: a case report - Sharudin, Siti Nurafiqah; Al Firdas, Ahmad Naufal Huda; Hitam, Shahrul; Hamid, Zubaidah; Othman, Noriah; Abd Rahman, Hayati; Arepen, Siti Asmat Md; Hassan, Eyzawiah; Norsham Juliana Nordin (Malaysian Journal Pathology, 2024)
Indexed by Scopus